Simulating the Arctic Tundra Battery performance at sub-zero temperatures - Heggeli, Erik (UiT Norges arktiske universitet, 2023)
The Arctic Tundra is an extremely cold desert-like environment. It is the home to many different species of animals and plants. With the oncoming threat of climate change, this biome is at risk of losing its biodiversity. This disruption of the Arctic Tundra caused by climate change, is what researchers at COAT with the assistance of UiT’s DAO project is trying to monitor. To be able to achieve this task, the DAO project is researching and creating Observation Units(Ous). These OUs need to tackle the challenges of withstanding the extreme condi- tions of the Arctic Tundra. These challenges are composed of the remoteness, where network availability and strength is poor or non-existing. Energy con- sumption where energy production or energy harvesting is challenging, and OUs will have to rely on a limited energy source like batteries. These OUs will observe in hard to reach places where trips for maintenance or data-collection will be time-consuming and challenging. To be able to design and build OUs that can be used in these conditions, the use of simulation is very valuable. With a good simulator, newly theorized solu- tions can be tested in conditions similar to the ones found in the Arctic Tundra. Using simulation will save time and resources. Long periods of time can be simulated in a fraction by simulation and the risk of losing hardware to failed deployments can be mitigated completely. This is where ESDS comes in, a sim- ulator with the purpose of simulating node networks found in cyber-physical systems, distributed systems. This simulator is still a work in progress and is not yet able to cover all the challenging aspects of the Arctic Tundra. This thesis focuses on what aspects are needed to be able to simulate this en- vironment. It focuses on the inclusion of the effects of extremely cold weather. To include this aspect in the simulator, a battery plugin is created. Batteries are directly affected by the ambient temperatures, causing the battery’s perfor- mance to aggravate at low temperatures. The ...